2010
DOI: 10.4141/cjss10026
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen- and phosphorus-based applications of cattle manure and compost for irrigated cereal silage

Abstract: E. 2010. Nitrogen-and phosphorus-based applications of cattle manure and compost for irrigated cereal silage. Can. J. Soil Sci. 90: 619Á635. Land application of livestock manure has caused concern about excess nutrients in soil and the potential risk to water quality. Application of manure based on cropnutrient requirements is considered a beneficial management practice. A field study was conducted to assess the feasibility and impact of crop-based N and P application rates of cattle (Bos taurus) manure and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 48 publications
1
30
3
Order By: Relevance
“…Both P and K in soil did not increase in the F treatment compared to the control; neither did they increase over time in the F treatment. This shows that both organic amendments added significant quantities of available P and K, more than inorganic fertilizer did, even though the target comparable value was N. This was in agreement with other researchers, who have reported that organic amendments added to soils targeting equivalent total N additions tend to overapply other nutrients, such as P and K. For example, Olson et al (2010) in their 6-year field study found that P-based manure application would require seven to ten times less manure than N-based application. Downloaded by [New York University] at 11:41 16 June 2015 Table 2 pH, electrical conductivity (EC), soil organic matter (SOM), Olsen P, and exchangeable K at the end of each of the 2 years of experiment EC SOM Olsen P…”
Section: Resultssupporting
confidence: 92%
“…Both P and K in soil did not increase in the F treatment compared to the control; neither did they increase over time in the F treatment. This shows that both organic amendments added significant quantities of available P and K, more than inorganic fertilizer did, even though the target comparable value was N. This was in agreement with other researchers, who have reported that organic amendments added to soils targeting equivalent total N additions tend to overapply other nutrients, such as P and K. For example, Olson et al (2010) in their 6-year field study found that P-based manure application would require seven to ten times less manure than N-based application. Downloaded by [New York University] at 11:41 16 June 2015 Table 2 pH, electrical conductivity (EC), soil organic matter (SOM), Olsen P, and exchangeable K at the end of each of the 2 years of experiment EC SOM Olsen P…”
Section: Resultssupporting
confidence: 92%
“…For example, Schlegel (1992) reported an increase in Bray-1 STP from an initial value of 13 to 67 mg kg −1 with the addition of composted beef cattle feedlot manure at 16.1 Mg ha −1 (N-based management) after 3 yr of annual applications. Similarly, greater STP with N-based management systems was reported by Toth et al (2006) for dairy manure, by Olson et al (2010) for cattle manure, and by Maguire et al (2008) for poultry litter, reflecting positive P balances.…”
mentioning
confidence: 90%
“…A 6-yr study of an irrigated triticale (Triticosecale spp. )-barley forage rotation found that the ANR from N-based beef cattle feedlot manure applied to a calcareous soil near Lethbridge, AB, was 15% (Olson et al, 2010b). We suspect that the greater recovery from the cattle manure probably resulted from irrigation boosting N mineralization, yield, and N uptake.…”
Section: Nitrogen and Phosphorus Recoverymentioning
confidence: 92%